Rapid Quantification of Bacteria in Infected Root Canals Using Fluorescence Reagents and a Membrane Filter: A Pilot Study on Its Clinical Application to the Evaluation of the Outcomes of Endodontic Treatment - Takuichi Sato; Keiko Yamaki; Naoko Ishida; Megumi Shoji; Emika Sato; Yuki Abiko; Kazuhiro Hashimoto; Yasuhisa Takeuchi; Junko Matsuyama; Hidetoshi Shimauchi; Nobuhiro Takahashi (International Journal of Dentistry)
Objective. The bacterial examination has been performed during the course of the root canal treatment. In the present pilot study, the new developed method, using fluorescence reagents and a membrane filter, was applied to the detection and quantification of bacteria in infected root canals, in order to evaluate the outcomes of the treatment. Methods. Six infected root canals with periapical lesions from 5 subjects were included. Informed consent was obtained from all subjects (age ranges, 23–79 years). Samples from infected root canals were collected at the beginning of the treatment (termed #25 First), the end of the first day of treatment (termed #55 First), and the next appointment day (termed #55 Second). Then, the bacterial count (CFU) was measured using fluorescence reagents (4′,6′-diamidino-2-phenylindole and propidium iodide) and the polycarbonate membrane filter by Bioplorer. Results. The mean ± SD of CFU in the sample of “#25 First” was (1.0±1.4)×105. As the root canal treatment progressed, the CFU decreased as 7.9×103 (#55 First) and 4.3×102 (#55 Second). Conclusion. In the present pilot study, rapid detection and quantification of bacteria in infected root canals were found to be successfully performed using fluorescence reagents and a membrane filter (Bioplorer analysis).